(untitled) (Journal of Medical Sciences, 2022)
CTAs, are a family of tumour-specific shared antigens that represent promising targets for cancer immunotherapy, as well as, diagnostic and prognostic markers for tumour development. T21 is a novel antigen with little information known about its protein expression in malignant cells. This study was aimed at evaluating the expression of T21 antigen as a potential diagnostic and prognostic marker for diverse malignancies. Material and methods: IHC staining was applied using a mono-specific polyclonal antibody against T21 to diverse paraffin-embedded malignant tissue microarrays. The specificity of the staining was confirmed by the negativity of the isotype controls. The slides were imaged to visualise the positive T21 staining using an inverted light microscope (x 10) with digital net camera. IBM-SPSS statistic software, version 22, was used for descriptive and statistical data analysis. Results: T21 was expressed in a large percentage of the examined primary (84.9%) and metastatic (65%) tumour sections. T21 expression was evident in ccRCC, adenocarcinoma of small intestine, testicular tumours, adenocarcinoma of rectum, squamous cell carcinoma of oesophagus and astrocytoma. For metastatic tumours, the expression was remarkable in metastatic squamous cell carcinoma of unknown origin, metastatic breast carcinoma and metastatic thyroid carcinoma. There was no correlation the between T21 expression and tumour staging. Conclusion: T21 represents a potential target for cancer immunotherapy and vaccination. Overexpression of T21 antigen represents a useful diagnostic biomarker for cancer progression, but caution should be used when considering its potential for use as a prognostic marker. Further inclusive work focusing on the correlation of T21 expression and tumour staging is needed.